Fasilitas Pernikahan Terpadu Di Pekanbaru Dengan Pendekatan Arsitektur Postmodern - Afriska, Karin; Amanati, Ratna; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The importance of an environment/event that is specifically to organize and focus its function to a wedding will make the couple easier to set a very sacred event and it is important towards a household that is the main goall of all couples.This buildings provides many function that is related and important to the event. From those functions, the couple who will get married should not be complicated to go to many places, it is only come to this environment/event. In designing, wedding facilities intergrated used postmodern architecture approach. The design of wedding facilities intergrated by applying the concept of dynamic, ethnic, and modern which is the basic concept for determining the design in accordance with the theme of postmodern. By the concept, wedding facilities intergrated can implement these apsects that can respond to the design, it can be order of mass, mass formation, and the application of contextual method. Contextual method which is seen as design technique that was developed to provide answers, especially on the conditions that are Regionalism, local context urbanism, respond to topogical condition, respond to environment, respect to given environment, and simbiosis man nature ,and culture.Key words: facility, wedding, intergrated, concept, postmodern, contextual, dynamic, ethnic, and modern